Intrinsic and extrinsic factors influencing career transitions - Ho, Mary Yanting (2008)
This study aims to find out the intrinsic and extrinsic factors that pull and push people into making career transitions. Career transition is defined as an expression of an intention, along with preliminary action, directed towards entering an occupation. Empirical research has shown that one changes job when one experiences a balance of “minus” over “plus” factors in one’s current occupations and perceives a balance of “plus” over “minus” factors in another occupation.